Is Health Education On Anemia Increasing Iron Supplementation Consumption In Adolescent Girls? : A Systematic Review - Berliana Farah Yanisah; Sri Widati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Approximately 1.62 billion people worldwide suffer from anemia, and about half of all anemia can result from iron deficiency. Adolescence is also considered the golden time for interventions to control anemia. It is also the right time to create a nutritional foundation for the labor of a child in the future. Nutrition education in schools has been shown to be effective in improving young people's knowledge, attitudes, and practices regarding anemia prevention. Objectives: This study aims to analyze the effects of iron supplementation and nutritional education on anemia in adolescent girls and the correlation with iron supplementation consumption so that anemia can be prevented as early as possible since adolescence. Discussion: This study showed that health education on anemia increases adolescents' knowledge and also weekly Iron–Folic Acid Supplementation (WIFS) health education can be effective in reducing the prevalence of anemia in adolescent girls by increasing the Hb level. Conclusions: These studies conclude that nutritional education increased the level of knowledge, attitude, and practice of adolescent girls and also led to an increase in Hemoglobin levels which can prevent anemia. Health education on anemia increase knowledge and practice of iron supplementation among adolescent girl. Increasing knowledge and practice in consuming iron supplementation will also increase the level of hemoglobin.